PROBLEMS OF INCREASING THE EFFICIENCY OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN THE REPUBLIC OF UZBEKISTAN (International journal of artificial intelligence, 2025)
Small business and private entrepreneurship play a vital role in the modern economic system and are actively supported by the state. However, challenges such as outdated technology, low financial literacy, bureaucratic barriers, and difficulties in obtaining credit hinder their development. To overcome these issues, it is proposed to establish the "Republican Center for Youth Entrepreneurship Support", which will include business incubators, a consulting and analytical center, and a youth economic support fund. This initiative aims to create favorable conditions for young entrepreneurs, improve business infrastructure, and contribute to sustainable economic growth.